Comparison of the Structured DSM–5 Clinical Interview for the Level of Personality Functioning Scale With the Structured Interview of Personality Organization. Issue 6 (2nd November 2018) - Kampe, Leonie; Zimmermann, Johannes; Bender, Donna; Caligor, Eve; Borowski, Anna-Lena; Ehrenthal, Johannes C.; Benecke, Cord; Hörz-Sagstetter, Susanne
Abstract: In Section III of DSM–5, the Level of Personality Functioning Scale (LPFS), a component of the DSM–5 Alternative Model for Personality Disorders (AMPD), offers a dimensional approach to the assessment of personality pathology. Similar to the psychoanalytic concept of personality organization developed by Kernberg (1984 ), personality disorders are assessed not only by categorical diagnoses, but also by measuring impairment of personality functioning. In this study we empirically investigate the convergence between two instruments examining personality functioning, the Structured Clinical Interview for the DSM–5 Alternative Model for Personality Disorders Module I (SCID-AMPD) and the Structured Interview of Personality Organization (STIPO). For this goal, correlations between both the overall scores of the two instruments as well as between the corresponding domain scale scores were examined. In addition, the relationship between interview ratings and clinical criteria quantifying the severity of the disorder (suicide attempts, frequency of psychiatric hospitalization, ICD–10 diagnoses) were analyzed. Based on videotaped assessments of 30 psychotherapeutic in- and outpatients with both instruments, significant correlations between overall scores and domain scales of the two interviews were found. Moreover, the ratings from both interviews showed high correlations with criteria of clinical severity.